Studi Kelayakan Bisnis Produk Cireng Stik Panir (Cistar) - M. Affrizal Miradji; Rohma Desi Ulfinda Sari; Grecencia Noyarto Dwiano; Ratih Purwati Ningsih; Sheli Rachmawati (Jurnal Kajian dan Penelitian Umum, 2025)
Cireng Stik Panir (CISTAR) is an entrepreneurial project of Accounting students at Universitas PGRI Adi Buana Surabaya in order to fulfill the assignment for the Business Feasibility Study course. This product is a snack innovation that combines traditional cireng made from tapioca flour with a spicy Indonesian shredded chicken filling, shaped like an ice cream stick, and coated with breadcrumbs to produce a crispy texture on the outside and chewy on the inside. The activity was carried out for two weeks (October 1 and 8, 2025) at UNIPA Dukuh Menanggal Campus II through direct sales and online marketing using WhatsApp and Instagram. The initial capital of IDR 200,000 was obtained from contributions from four team members, with an effective production cost of IDR 112,230 for 40 pcs, resulting in a COGS of IDR 2,806 per pc and a profit of IDR 26,570 (margin ≈26%). The SWOT analysis shows strengths in the uniqueness of taste and shape, great opportunities in the spicy snack and frozen food market, but has weaknesses in product durability and the threat of intense competition. This project successfully developed students' financial independence, entrepreneurial spirit, decision-making skills, and creativity through hands-on experience in production, distribution, marketing, and consumer interaction. CISTAR has the potential to develop into a sustainable business through innovative flavors and expanded sales channels.